IoT-Based lab system for teaching methods in times of crisis - Motakabber, S. M. A.; Syed Ahmad Fawwaz Wafa, Syed Ridza, (AlamBiblio Publishers, 2021)
The revolution of communication technology has enabled people to communicate easily with others and perform many tasks from a distance. The Internet plays an important role in communication and helps to perform tasks and make people's lives easier. It led to the introduction of the Internet of Things (IoT) technology, where physical objects are connected to the Internet to perform a specific task. So that IoT can be a valuable tool in times of crisis, most modern industries can produce their products automatically and remote monitor and control the system. The same technique can be applied to overcome face-to-face teaching in science and engineering education during times of crisis. This research proposes the design and development of an IoT-based hands-on laboratory system that can be operated remotely. The methodology has been implemented and worked based on the concept of virtual reality. The research has been carried out for two simple electrical laboratory experiments: the basic logic gate and Ohm’s Law experiment. The experimental results show that the system can be implemented since the results obtained are satisfy their theoretical results. Furthermore, an improvement can be made so that the system can be integrated with the Internet and the system can function efficiently.